Forest plantation effects on carnivore guilds composition and structure - Teixeira, Daniela Filipa Ferreira (2023)
Eucalyptus spp. are known worldwide due to the global distribution of their forestry plantations, which cover almost 22 million hectares outside their native area. Species of these genera are commonly planted, aiming to provide resources for the wood and paper industries. The negative impacts that Eucalyptus plantations may cause on the environment and wildlife have been studied by the scientific community in many regions of the world. However, in countries like Portugal, information regarding the effects of these exotic plantations on the mammalian fauna is still scarce. This knowledge is important for a sustainable management of Eucalyptus plantations. The present thesis aims to help fill this knowledge gap by studying the effects of Eucalyptus globulus plantations on mammal populations, especially mesocarnivores, at different geographical scales. It intends to provide information that will allow to adapt/enhance the current management of these plantations in Portugal to conciliate forestry production and nature preservation. Therefore, in chapter two, we reviewed studies reporting carnivore use of exotic Eucalyptus plantations to identify the general life-history traits of the species found in those anthropic systems worldwide. Results indicate that habitat generalist carnivores are more likely to use Eucalyptus plantations than specialist species. In chapter three, by using the available data on mesocarnivore distribution in continental Portugal, we concluded that Eucalyptus plantations negatively affect the distribution patterns of the five study species (red fox Vulpes vulpes, European badger Meles meles, Stone marten Martes foina, common genet Genetta genetta, and Egyptian mongoose Herpestes ichneumon). Moving down to a regional scale, in chapter four, we identified the effects of several drivers on the relative abundance of rodents inhabiting Eucalyptus plantations, using data collected through a capture-recapture approach using Sherman traps. Results showed no significant detectable effect of Eucalyptus plantations on rodents’ relative abundance (i.e., other environmental factors seem to be more influential). The fifth chapter evaluated the influence of environmental drivers on the occupancy patterns of red foxes based on camera trapping data. It showed that this mesocarnivore preferred to use native vegetation over non-native plantations (including Eucalyptus plantations) during their activities. Finally, chapter six analysed the temporal and spatio-temporal activity and the coexistence patterns of red foxes and stone martens. Results indicate that human disturbance contexts, such as plantations, influence both mesocarnivores’ spatio-temporal and coexistence patterns, with species showing changes in those patterns to minimise contact with humans and their disturbance. Overall, the results of this thesis indicate that Eucalyptus plantations and the activities related to these highly disturbed systems affect the ecological patterns of mammal species in Portugal, although some species are still able to use these anthropic systems. Therefore, it is necessary to promote management measures that may allow conciliating forestry activities and biodiversity conservation, thus promoting more sustainable harvesting of these plantations. This can be achieved, for example, through the protection of native habitats remnants that still subsist within plantations, the protection of local faunal communities, and the spatio-temporal compatibilization of anthropogenic impacts with the critical periods and areas for wild populations (e.g., reproduction, feeding and refuge areas and daily periods).